Book review:M. JEFFREYS – M. D. LAUXTERMANN (eds.), The Letters of Psellos. Cultural Networks and Historical Realities [Oxford Studies in Byzantium], Oxford 2017 - GRUNBART, Michael (Byzantina Symmeikta, 2019)
Book review:M. Jeffreys – M. D. Lauxtermann (eds.), The Letters of Psellos. Cultural Networks and Historical Realities [Oxford Studies in Byzantium], Oxford 2017, pp.468. ISBN 978-0-19-878722-8